Faktor-faktor yang Memengaruhi Nilai Tukar Petani (NTP) di Indonesia - Suci Syifa Aulia; Dyah Sulistiyo Rimbodo; Muhammad Ghafur Wibowo (Universitas YARSI, 2021)
This study aims to determine the factors that can affect the level of welfare of farmers in Indonesia by using the Farmer Exchange Rate (NTP) indicator from 2010-2019. The variables used in the study are those that have a big influence on the increase or decrease in the agricultural sector economy. These variables are the Consumer Price Index (CPI), the current price food GDP variable and the rice price variable. Research data includes secondary data which can be obtained from the Indonesian Central Bureau of Statistics (BPS), Bulog, the Ministry of Agriculture and other news related to research. The results showed that the CPI variable in the long term had a positive and significant effect on farmer exchange rates. The higher the Consumer Price Index, the higher the price of goods and services, especially rice, in the market. This causes farmers' income to increase which has an impact on the welfare of farmers, especially rice farmers. The GDP variable has a positive and significant effect on the farmer exchange rate. High GDP causes farmer welfare to increase in the short term. The rice price variable has a negative and significant effect on the farmer exchange rate. If the price of rice rises with fixed or increased production costs, the farmer's income will decrease.